Mothers and food advertising directed at children: perceptions and experiences - Luciana Castronuovo; Patricia Gutkowski; Victoria Tiscornia; Lorena Allemandi (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2016)
The objective of this study is to analyze how food advertising is perceived by mothers from different socioeconomic sectors of the Metropolitan Area of Buenos Aires, Argentina. Between May and November 2015, eight focus groups were conducted with the participation of 49 mothers of different education levels living in the study area. The results show how the purchasing decisions of mothers are influenced by the requests of their children, which are in turn prompted by food advertising and promotion. The study also shows how food advertising and promotion are combined with other environmental factors (greater supply of food products, "more demanding" children) that affect the decision-making process of mothers regarding their children's nutrition and foster the consumption of certain unhealthy products. This situation was observed in all the focus groups, without differences among education levels.